BODYWEIGHT SQUAT EXERCISE AS AN EFFECTIVE INTERVENTION TO ENHANCE MUSCLE STRENGTH IN OLDER ADULTS - Fitriani, Aidah; Sutria, Eny; Rasmawati, Rasmawati; sumarmi, sumarmi; Ngoc, Vu Thi (NurseLine Journal, 2026)
Background: Aging is associated with a significant decline in muscle mass and strength, which increases the risk of falls among older adults. One strategic approach to address this issue is bodyweight squat training, which targets lower extremity muscle strength, balance, and functional ability in older adults. This study aimed to analyze the effect of bodyweight squat training on muscle strength in older adults. Methods: This quantitative study employed a pre-experimental design using a one-group pre-test and post-test approach. A total of 63 older adults were recruited using a purposive sampling technique. Muscle strength was assessed using the Five Times Sit-to-Stand Test (FTSST). Data were analyzed using the paired sample t-test. Results: The findings demonstrated a significant improvement in muscle strength following bodyweight squat training (p = 0.001). The mean FTSST completion time decreased from 12.51 seconds at baseline to 10.86 seconds after the intervention. Conclusion: The reduction in FTSST completion time indicates that bodyweight squat training is effective in improving muscle strength in older adults. This exercise can be recommended as a routine physical activity to enhance muscle strength and reduce the risk of falls.